Perilaku pengelolaan keuangan ibu rumah tangga penerima remitansi - Sulistiani, Sulistiani; Prajawati, Maretha Ika (Maliki Interdisciplinary Journal, 2026)
This study examines the financial management behavior of housewives receiving remittances in Tangkisan Village, a community of migrant traders who regularly receive remittances from family members. Using a qualitative descriptive approach, the research explores how remittances are managed through in-depth interviews with several informants. The study’s results show that remittances are not only used for consumption needs but are also allocated for business capital, traditional investments such as gold, and symbolic expenditures influenced by social pressure. Analysis of the findings using the Theory of Planned Behavior, Mental Accounting Theory, and the Family Financial Socialization Model indicates that attitudes, subjective norms, perceived control, as well as family financial socialization experiences play a significant role in shaping remittance management decisions. This study emphasizes that improving financial literacy and empowering women are important factors in maximizing the benefits of remittances for household economic resilience.